Providing assistance to convicts as the basis for effective work to prevent recidivism - I.A. Efremova; A.N. Varygin (Известия высших учебных заведений. Поволжский регион: Общественные науки, 2023)
Background. The relevance of the stated topic is reflected in the steady growth of recidivism, which requires effective measures to prevent it. The purpose of the study is to analyze the provision of assistance to convicts as the basis for effective work on the prevention of recidivism and to develop directions for improving this activity. Materials and methods. The article used normative legal acts, draft laws, statistical data and scientific works on the problem under study. The methodological basis was the comparative legal and formal-logical research methods, analysis and synthesis, induction and deduction, logical, systemic, structural-functional, linguistic, formal-legal. Results.The analysis of problems of prevention of recidivism of crimes committed by persons released from places of imprisonment is carried out. It is noted that such preventive activities and their effectiveness are primarily related to the issues of social adaptation of persons released from prison. Two main stages of social adaptation of these persons are defined: penitentiary and postpenitentiary, specific measures implemented within each of them are considered. Conclusion. The necessity of using all possible forms and methods of providing assistance to persons released from prison is justified, and most importantly – drawing the attention of the legislator to this problem, the adoption of an appropriate federal law, the need for which scientists have been talking for many years.